Interactive Relationship between Stressors and Maladaptive Cognitive Coping in Predicting Depressive Symptoms - Ali Mohammadzadeh-Ebrahimi; Tayebe Rahimi-Pordanjani (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objective: Depression is among most disabling mental disorders and its prevalence is increasing. Identifying the risk factors and understanding the process of developing depressive symptoms is essential for prompt prevention and early interventions. The present study aimed to determine the interactive relationship between stressors and maladaptive strategies of cognitive coping in predicting depressive symptoms. Materials and Methods: This descriptive correctional study was conducted with participation of 373 students of Shahid Chamran University in the first semester of 2014-2015. Stratified random sampling was used for selecting participants. Life Experiences Survey questionnaire, Cognitive Emotion Regulation questionnaire, and Beck Depression Inventory-second edition were used for data collection. Data were analyzed by the multiple regression analysis with the SPSS-24 software. Results: The mean (SD) stressors score was 19.9 (10.1), maladaptive strategies of cognitive coping 39.4 (7.4), and depressive symptoms 11.5 (6.9). The β value for stressors was 0.51, Maladaptive Cognitive Coping 0.24 and their interactions 0.11 (P< 0.01). The variance of maladaptive strategies of cognitive coping was 5.2% (P<0.01). Stressors and maladaptive strategies of cognitive coping created 3% of the increased variance for the model, which indicates that these variables have a meaningful interaction with each other in predicting of depressive symptoms (P< 0.01). Conclusion: Participants who used more maladaptive strategies of cognitive coping subsequent to encountering stressors tend to show more depressive symptoms and vice versa. Therefore, intervention and prevention programs should focus on identifying and modifying the maladaptive strategies of cognitive coping as well as training and acquiring adaptive strategies of cognitive coping.